Prevalence of colorectal polyps in patients undergoing colonoscopy in Sulaimaniyah gastroenterology center: a retrospective study - Hawar Ali Ghalib; Fadhil Ahmed Mohialdeen Khayat; Chenar Dhahir Fatah (Advanced Medical Journal)
Background & objectives: Colorectal cancers are believed to develop primarily through an adenoma-carcinoma sequence, with adenomatous polyps beginning as the primary precursor lesions. Thus, this study aimed to assess the prevalence of colorectal polyps with their characteristics and relation to age/gender and to aid in establishing a screening program to detect polyps and colorectal cancer in the early stages.